Batillipes pennaki Marcus, 1946 (Arthrotardigrada: Batillipedidae): deciphering a species complex - Santos, Erika; Veiga, Puri; Rubal, Marcos; Bartels, Paul J.; Da Rocha, Clélia M. C.; Fontoura, Paulo (Zootaxa, 2019)
Batillipes pennaki has been considered a common and a cosmopolitan marine tardigrade species. However, the original diagnosis of this species is very incomplete, and consequently there is a high probability of incorrect records. Therefore, a comparative analysis of quantitative and qualitative morphological characters among eight different populations from the Atlantic basin was done in this study to investigate if B. pennaki is a complex of similar species, each with a restricted distribution range. The result of discriminant analyses showed clear morphometric differences between populations that were arranged into three main groups, distinguishing Western Atlantic populations, Eastern Atlantic populations and a Mediterranean population. Furthermore, the result of analyses of morphological structures revealed peculiarities of some traits with taxonomic relevance, such as leg IV sensory organs and primary clavae, consistent with the clusters revealed by quantitative data, allowing us to distinguish three different pseudocryptic species and supporting the hypothesis that B. pennaki is a species complex.